A self-consistent model for the evolution of the gas produced in the debris disc of β Pictoris. Issue 1 (8th June 2016) - Kral, Q.; Wyatt, M.; Carswell, R. F.; Pringle, J. E.; Matrà, L.; Juhász, A.
Abstract: This paper presents a self-consistent model for the evolution of gas produced in the debris disc of β Pictoris. Our model proposes that atomic carbon and oxygen are created from the photodissociation of CO, which is itself released from volatile-rich bodies in the debris disc due to grain–grain collisions or photodesorption. While the CO lasts less than one orbit, the atomic gas evolves by viscous spreading resulting in an accretion disc inside the parent belt and a decretion disc outside. The temperature, ionization fraction and population levels of carbon and oxygen are followed with the photodissociation region model cloudy, which is coupled to a dynamical viscous α model. We present new gas observations of β Pic, of C i observed with Atacama Pathfinder EXperiment and O i observed with Herschel, and show that these along with published C ii and CO observations can all be explained with this new model. Our model requires a viscosity α > 0.1, similar to that found in sufficiently ionized discs of other astronomical objects; we propose that the magnetorotational instability is at play in this highly ionized and dilute medium. This new model can be tested from its predictions for high-resolution ALMA observations of C i . We also constrain the water content of the planetesimals in β Pic. The scenario proposed here might be at play in all debris discs and this model could be used more generally on all discs with C, O or CO detections.